DC flashover performance of ice‐covered insulators under complex ambient conditions. Issue 10 (1st July 2016) - Hu, Yuyao; Jiang, Xingliang; Shu, Lichun; Zhang, Zhijin; Hu, Qin; Hu, Jianlin
Abstract : The electrical characteristics of ice‐covered insulators in coexisting conditions of high altitude, icing and pollution are a basis for external insulation selection of transmission lines in icing regions. Ice accretion on insulators has been studied for decades, while few studies focus on the flashover performance of ice‐covered insulators polluted by two types of contamination, that is the solid layer method and icing water conductivity method, simultaneously. On the basis of the investigations on DC flashover performance of ice‐covered insulators in the artificial climate chamber, the influence of different parameters, such as insulator string length, icing water conductivity, salt deposit density as well as atmospheric pressure on DC icing flashover voltage of insulator strings is studied. According to the experimental results, the relationships between the flashover voltage and each of such factors are determined and analysed. Moreover, the correction formula for DC flashover voltage of ice‐covered insulators in complex ambient conditions is proposed.